The p53/miR-145a Axis Promotes Cellular Senescence and Inhibits Osteogenic Differentiation by Targeting Cbfb in Mesenchymal Stem Cells - Xia, Chao; Jiang, Tianyuan; Wang, Yonghui; Chen, Xiaoting; Hu, Yan; Gao, Yanhong (Frontiers in Endocrinology, 2021)
The osteogenic differentiation capacity of senescent bone marrow mesenchymal stem cells (MSCs) is reduced. p53 not only regulates cellular senescence but also functions as a negative regulator in bone formation. However, the role of p53 in MSCs senescence and differentiation has not been extensively explored. In the present study, we investigated the molecular mechanism of p53 in MSCs senescence and osteogenic differentiation. We found that p53 was upregulated during cellular senescence and osteogenic differentiation of MSCs respectively induced by H2O2 and BMP9. Similarly, the expression of p53-induced miR-145a was increased significantly. Furthermore, Overexpression of miR-145a in MSCs promoted cellular senescence and inhibited osteogenic differentiation. Then we identified that p53-induced miR-145a inhibited osteogenic differentiation by targeting core binding factor beta (Cbfb), and the restoration of Cbfb expression rescued the inhibitory effects of miRNA-145a. In summary, our results indicate that p53/miR-145a axis exert its functions both in promoting senescence and inhibiting osteogenesis of MSCs, and the novel p53/miR-145a/Cbfb axis in osteogenic differentiation of MSCs may represent new targets in the treatment of osteoporosis.